sLZIP functions as a key modulator of bone remodeling by regulating the crosstalk between osteoblasts and osteoclasts - Sungyeon Park; Jeonghan Kim; Jesang Ko (Experimental and Molecular Medicine)
Abstract Human small leucine zipper protein (sLZIP) regulates the differentiation of both osteoblasts (OBs) and osteoclasts (OCs). However, the regulatory role of sLZIP in bone remodeling and its involvement in bone disorders remain unclear. Here we investigated the role of sLZIP in bone remodeling and its importance in the development of cell therapies for bone diseases. sLZIP increased bone mass in an osteoporosis mouse model. Moreover, bone mass was lower in mesenchymal stem cell-specific murine LZIP-1/2 knockout (Osx-LZIP-1/2fl/fl) mice than in control LZIP-1/2fl/fl mice. Compared with control mice, Osx-LZIP-1/2fl/fl mice presented delayed bone fracture healing in osteoporosis. Conditioned medium from OBs differentiated from adipose-derived stem cells from Osx-LZIP-1/2fl/fl mice attenuated OC formation and the migration of bone marrow-derived macrophages. However, conditioned medium from OCs from sLZIP transgenic mice induced OB differentiation and migration. sLZIP regulates the secretion of OC-derived sphingosine-1-phosphate, which induces OB differentiation. sLZIP also regulates OB-derived WNT16, which inhibits OC differentiation. Therefore, sLZIP is a key modulator of the crosstalk between OBs and OCs and promotes bone remodeling and fracture healing in osteoporosis. In addition, sLZIP-overexpressing adipose-derived stem cells promote bone formation and repair in osteoporosis. sLZIP is an excellent target for stem cell-based treatment of osteoporosis.